Effect of Different Stimulus Polarities on Wave V of Auditory Brainstem Response in Evaluation of Hearing - Kashmala Munawar, Sanaullah Bhatti, Saba Islam, Muhammad Azeem Aslam, (Pakistan Journal of Medical & Health Sciences, 2024)
Objectives: To evaluate the effect of stimulus polarity on latency and amplitude of wave V by click generated auditory brainstem response and to evaluate the effect of rarefaction and condensation on wave V latency and amplitude Methodology: This interventional study was conducted at Al-Nafees Teaching Hospital Islamabad and Bahwal Victoria Hospital Bahawalpur from January 2019 to June 2019. Sixty patients with the complaint of hearing loss were enrolled. Results: There were 26 (43.3%) males and 34 (56.7%) were females. The mean amplitude of wave V of 358.33 nV when rarefaction was applied and 336.33 nV when condensation was used. There was a significant (P<0.05) difference in mean value of amplitude and latency varying stimulus polarity. Conclusion: The latency and amplitude of wave V are affected by changing stimulus polarity Keywords: Effect, Stimulus polarities, Wave V, Auditory brainstem response, Hearing